Process Methodology for Emergency Management - Ludík, Tomáš; Ráček, Jaroslav (Environmental Software Systems. Frameworks of eEnvironment, 2011)
Emergency management is represented by managerial functions which aim to reduce vulnerability to hazards and to cope with disasters. Emergencies often have direct impact on the environment. This paper focuses on identification and subsequent software support processes in the emergency management. The paper aims to describe a process methodology for emergency management in details. The methodology describes how to manage an information system development suitable for emergency management, which is built on business processes. The methodology consists of five main phases. Each phase is described in terms of individual activities, work products, and user roles. The next part of the paper recommends the use of particular technologies, tools and resources that have been successfully proved in the analysis of emergency situations in the Czech Republic. The straightforward outcome of the novel process methodology is more effective solution of emergency situations and therefore the reduction of negative environmental impacts.